Trauma in selected Eastern African fiction and life writing on Civil Wars, 2000 - 2014 - Tembo, Nick Mdika Hubert (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.